2022
DOI: 10.6007/ijarbss/v12-i2/12189
|View full text |Cite
|
Sign up to set email alerts
|

Global Financial Trading Strategies: A Bibliometric Analysis of the Indexed Publications in Scopus between 2001– 2021

Abstract: A trading strategy is merely a technique that determines the criteria under which securities can be purchased or sold in a financial market. When it comes to trading strategy, there are two strategies that are commonly used, technical analysis and fundamental analysis. This paper shows a bibliometric analysis of the publications related to trading strategies. The objective is to ascertain and evaluate the contribution of the past studies in the financial trading strategy domain. According to findings, the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Following quantitative tools under bibliometric analyses have been used in this research. The tools of publication related metrics (total publications), total citation analyses, countries analysis, author analysis, source title analysis, authorship analysis, keyword analysis and co-occurrence analysis has been used [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following quantitative tools under bibliometric analyses have been used in this research. The tools of publication related metrics (total publications), total citation analyses, countries analysis, author analysis, source title analysis, authorship analysis, keyword analysis and co-occurrence analysis has been used [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…From 2001 to 2021 duration, the United States leads all other nations with 86 publications, followed by the United Kingdom with 50, China with 43, Taiwan with 27, Australia, and Germany with 17 apiece. However, the keyword analysis shows that research on stock options and index options is extremely limited [22]. In a study, the role of technological progress in the Russian economy was shown through the use of FinTech and the development of human capital, the change of business processes based on modern financial technologies, the creation of new, promising opportunities, and the response to the challenges of Industry 4.0 [28].…”
Section: Theme 1: Volatility and Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kajian yang lebih panjang dan penglibatan lebih banyak mata wang diperlukan untuk melihat kesannya terhadap pasaran FOREX secara holistik. Untuk kajian di masa hadapan, penyelidik disarankan untuk mengambil kajian ini sebagai titik permulaan untuk meneroka lebih banyak dapatan kajian dengan penggunaan indikator analisis teknikal yang lain, atau dengan menggunakan kaedah pembelajaran berasaskan mesin (machine learning) yang banyak digunapakai oleh pedagang dan pelabur masa kini (Shafie & Yaacob 2022).…”
Section: Kesimpulanunclassified